The corruption-income inequality trap: A study of Asian countries - Inayati Nuraini Dwiputri; Lincolin Arsyad; Rimawan Pradiptyo (Kiel Institute for the World Economy (IfW), 2018)
The existence of ambiguity in the study of the impact of corruption on economic growth, namely the grease the wheel hypothesis and sand the wheel hypothesis, trigger this research to look at the impact of corruption through another perspective, i.e. income inequality. This study identifies the mutual influence between corruption and income inequality in Asian countries, because in general, Asian countries have high levels of corruption and poor governance. This research attempts to contribute literature on the theoretical modeling of the effect of corruption on income inequality, using the Ramsey Growth model's development. Using the Ordinary Least Square (OLS), Tobit, and Two Stage Least Square (2SLS) methods, this study also proves that a reciprocal influence exists between corruption and income inequality in Asia, otherwise known as the corruption-inequality trap. The results show that the higher the level of corruption is, this can aggravate income inequality, and the higher the income inequality level is, this can affect the level of corruption in Asian countries. Other variables that have a robust effect on income inequality in Asia are per capita income, the gross enrollment rate in primary education, population growth, foreign direct investment, and governance.
http://dx.doi.org/10.7910/DVN/8VF8RV
Keywords: D63; D73; O11; 330; economic growth; income inequality; corruption; grease the wheel hypothesis; sand the wheel hypothesis